ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT PENGANGGURAN DI KABUPATEN MIMIKA - Prediman Paelongan; Stepanus Sandy (JURNAL KRITIS (Kebijakan, Riset, dan Inovasi), 2019)
The purpose of this study was to determine the significance of the effect of economic growth rates and wage levels on the unemployment rate in Mimika Regency. This study uses associative methods with multiple linear regression analysis tools. The data used in this study are secondary data obtained from BPS Mimika Regency, which consists of data on economic growth rates, wage rates, and unemployment rates during the years 2010-2017. Based on the results of this study, it is known that: (a) economic growth variables have no significant effect on unemployment rates in Mimika Regency; (b) wage level variables have a significant effect on the unemployment rate in Mimika Regency; and (c) economic growth variables and wage rates simultaneously have a significant effect on the unemployment rate in Mimika Regency.